Debt relief reforms are not enough to alter the relations of inequality and harm reproduction: the case of educational debt and the need for structural reconstruction - Barak, Gregg (Critical criminology, 2022)
In the contemporary age of financialization, more and more citizens of the world are living in debt bondage and finding themselves subject to those financial institutions that are endangering the global political economy. At this turning point in global capitalism, even if the "one percent" provided "clean slates" for the debtors of the world, which has occurred many times in human history, the current economic polarization will continue to intensify so long as the contradictions of unsustainable capital accumulation are not resolved. In order to avoid a futuristic neo-serfdom, where people are not tied to the land, but are free to live wherever, though they are unable to make ends meet anywhere, structural reconstructions of our political economies are necessary. Using higher education and the student-loan debt crisis in the United States as its focus, this article makes the case for student relief rather than for student distress, especially for marginalized consumers. This investigation is not about state-financial criminality per se. More appropriately, it is about social harm in the tradition of zemiology.